Signaling motives in lying games - Tilman Fries (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2021)
This paper studies the implications of agents signaling their moral type in a lying game. In the theoretical analysis, a signaling motive emerges where agents dislike being suspected of lying and where some types of liars are more stigmatized than others. The equilibrium prediction of the model can explain experimental data from previous studies, in particular on partial lying, where some agents dishonestly report a non payoff-maximizing report. I discuss the relationship with previous theoretical models of lying that conceptualize the image concern as an aversion to being suspected of lying. The second half of the paper tests the theoretical predictions in an experiment. In contrast to previous literature, the experimental results show no evidence that image concerns influence lying behavior in the laboratory.
Keywords: C91; D82; D90; 330; lying; image concerns; honesty; experiment